161k views
4 votes
Is the equation 3(2 x-4)=-18 equivalent to 6 x-12=-18 ?Yes, the equations are equivalent by the Associative PropertyYes, the equations are equivalent by the Commutative ProperYes, the equations are equivalent by the Distributive Property.No, the equations are not equivalent.

Is the equation 3(2 x-4)=-18 equivalent to 6 x-12=-18 ?Yes, the equations are equivalent-example-1

1 Answer

4 votes

Answer:

Yes, the equations are equivalent by the Distributive Property.

Step-by-step explanation:

Given the equation:


3(2x-4)=-18

Opening the bracket on the left-hand side, we have::


\begin{gathered} 3(2x-4)=-18 \\ \implies6x-12=-18 \end{gathered}

Therefore, we conclude that the equation 3(2x-4)= -18 equivalent to 6x-12=-18 by the Distributive Property.

Recall: By the distributive property:


a(b+c)=ab+ac

User MHD Alaa Alhaj
by
6.1k points